2004
DOI: 10.1002/jctb.1128
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of photocatalytic oxidation of gaseous 2‐propanol using thin‐film TiO2 photocatalyst

Abstract: This work presents a photocatalysis-based method to treat and purify air because of its broad applicability to common, oxidizable, air contaminants. The effect of oxygen content, temperature, water vapor, and 2-propanol concentration on the TiO 2 surface was investigated. The rate of 2-propanol decomposition increased with increasing the oxygen content, but was reduced at temperatures higher than 100• C. When water vapor concentration was in the range of 10-355 mmol m −3 , the rate of 2-propanol decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Several studies have shown the importance of gas phase O 2 in the conversion of 2-propanol to acetone [721,722,[898][899][900][901][902][903][904]. In particular, Brinkley and Engel [900][901][902] examined the photooxidation of 2-propanol on R TiO 2 (110) and (100) surfaces in UHV, and concluded that O 2 was necessary for photooxidation.…”
Section: Alcoholsmentioning
confidence: 97%
See 3 more Smart Citations
“…Several studies have shown the importance of gas phase O 2 in the conversion of 2-propanol to acetone [721,722,[898][899][900][901][902][903][904]. In particular, Brinkley and Engel [900][901][902] examined the photooxidation of 2-propanol on R TiO 2 (110) and (100) surfaces in UHV, and concluded that O 2 was necessary for photooxidation.…”
Section: Alcoholsmentioning
confidence: 97%
“…Isopropyl alcohol: Photooxidation of 2-propanol (isopropanol) presents an interesting case because the reaction exhibits near 100% selectivity toward acetone [721,722,[898][899][900][901][902][903][904]. Conversion of 2-propanol to acetone requires two oxidative steps, and the intermediate associated with the first step has not that been identified.…”
Section: Alcoholsmentioning
confidence: 98%
See 2 more Smart Citations
“…Titanium dioxide (TiO 2 ) is a widely studied material because of its unique optical, electrical and chemical properties, high photocatalytic activity and high photoelectric conversion efficiency. It is well known for its photovoltaic and photocatalytic properties 1–4. Polyaniline (PANI) is one of the most intrinsically conducting polymers, with perfect conductivity, good environmental stability and relatively easy preparation.…”
Section: Introductionmentioning
confidence: 99%